Directed evolution of the CpcA biosynthetic pathway and optimization of conditions for CpcA production and its properties - Dong, Dalu; Pan, Hangtao; Yu, Ping (Applied microbiology and biotechnology, 2014)
To improve the production of phycocyanin holo-α-subunit (CpcA) from Spirulina maxima , five genes and their spacer region sequences involved in its biosynthesis were subject to the directed evolution by error-prone PCR using the plasmid pETDuet-6 as the template. Mutants were screened by determining the CpcA yield in 96-well plates directly. A mutant strain CPCA 713 with the highest CpcA yield of 17.36 mg/l in 96-well plates was obtained, and this yield was 29.7 % higher than that from the control strain ZJGSU09 containing pETDuet-6 (13.38 mg/l). Sequence alignments indicated that 10 nucleotides and 5 amino acids were mutated. Glycerol and beef extract were found to be the best carbon and nitrogen sources for accumulating CpcA in the screened CPCA 713 strain, respectively. The concentrations of the key factors that affected the CpcA yield were optimized by response surface methodology with a Box–Behnken design and were as follows: glycerol, 16.0 g/l; yeast extract, 18.2 g/l; and beef extract, 4.8 g/l. Under the optimal conditions, the CpcA yield was up to 71.21 mg/l in the shake flask. Time-course of the CpcA production before and after optimization were performed and compared. After being purified by a Hi-Trap metal chelating affinity column loaded with 100 mM nickel sulfate, CpcA presented a single protein band with an estimated molecular weight of 29 kDa in the sodium dodecyl sulfate polyacrylamide gel electrophoresis gel. The purified CpcA had the maximal absorptive and fluorescent emission wavelengths at 623 and 650.8 nm, respectively, and was stable at temperatures of 40 °C below and pHs of 5.5–8.0, and in the dark or in the dim light. It had also a strong scavenging ability to three free radicals ·OH, ·O 2 – , and di(phenyl)-(2,4,6-trinitrophenyl)iminoazanium (DPPH). The IC 50 values of ·OH, ·O 2 − , and DPPH free radicals by purified CpcA were 0.08, 0.46, and 0.48 mg/ml, respectively. This study lays a good foundation for the industrial production of CpcA by engineered Escherichia coli in future.